Field reports form submitted by Carl J. Bendorf, winter 1983-1984 - Bendorf, Carl J.et al (1983)
Field reports form was submitted by Carl J. Bendorf, winter 1983-1984. Other observers were Thomas J. Kent, Thomas J. Staudt, and Richard Jule Hollis. They reported that a Cooper's Hawk and two Northern Goshawks were sighted in Johnson County, a Golden Eagle in Jasper County, a Northern Saw Whet Owl and Varied Thrush in Davenport, and 300 Snow Buntings in Dysart, Iowa. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1983-1984. Epson - sheet feed